(untitled) (Proceeding of the International Conference on Arts and Humanities, 2019)
“I am a camera.” First line of Berlin Stories, Christopher Isherwoods Cities transcend familiar rhythms; they are neither conservative nor modern – rather; they are both. Urban subjectivity is a reaction to being exposed to difference and complexity which divides perception. With this research, I would like to address the urban account of interiority within the city; the subjective feeling linked to an exterior condition, the issue of the inside-outside divide that is made by the street rather than removed from it. This is between the enclosure of a physical space, inner and the subjective, outer and the more physical, the self and the city; and the ambiguous interior-exterior boundaries of its citizens. According to Richard Sennet, a sociologist, identity can be defined as the image that people have of you and that you may have of yourself that comes of constant interchange of yourself with your surroundings. Where is this more dynamic, complex form of identity found in the city? In order to get an in depth understanding of the urban field I will dwell into the exact agents/ players that constitute it. Using a psychogeographic approach, this project will understand the space and the constructs that form when a person interacts, enters, demarcates and starts forming enclosures both physical and nonphysical.